KOMPETENSI SUMBER DAYA MANUSIA DAN PENGARUHNYA TERHADAP KINERJA KARYAWAN SEKTOR UMKM INDUSTRI PERHOTELAN DIKABUPATEN KUANTAN SINGINGI - Anang Adri; Zulfadil Zulfadil; Rifqi Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of human resource competence and its influence on the performance of employess of the hotel Industry in Kabupaten Kuantan Singingi Regency. The population in this study includes all employees in Hotel amounting to 50 people. And primary data were collected using a questionnaire as an instrument to prove the results of the research, to test the hypothesis in this study was to use multiple linear regression analysis with of SPSS. The sampling technique that has been selected is the census method (50 employees of the Hotel Kuantan Singingi Regency). The results showed that: 1) knowlegde has a positive and significant influence of Knowledge on the performance of employees in the Hotel Industry in Kabupaten Kuantan Singingi Regency, 2) Skills has a positive and significant effect on employee performance in the Hotel Industry in Kabupaten Kuantan Singingi Regency, 3) Ability has a positive and significant effect. significant towards the employee performance of the Hotel Industry in Kabupaten Kuantan Singingi Regency, 4) Knowledge, skills, and abilities simultaneously have a positive and significant effect on the employee performance of the Hotel Industry in Kabupaten Kuantan Singingi Regency.Keywords : Knowledge, Ability, Skills, dan Employee Performance